2022
DOI: 10.3390/molecules27051466
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antibacterial Properties of Oligomeric Dehydrogenation Polymer from Lignin Precursors

Abstract: The lignin precursors of coniferin and syringin were synthesised, and guaiacyl-type and guaiacyl-syringyl-type oligomeric lignin dehydrogenation polymers (DHP and DHP-GS) were prepared with the bulk method. The carbon-13 nuclear magnetic resonance spectroscopy showed that both DHP-G and DHP-GS contained β-O-4, β-5, β-β, β-1, and 5-5 substructures. Extraction with petroleum ether, ether, ethanol, and acetone resulted in four fractions for each of DHP-G (C11–C14) and DHP-GS (C21–C24). The antibacterial experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…4(A), indicating the presence of a G-type dimer structure linked by a β-5 bond (phenyl-coumaran). 49,54…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4(A), indicating the presence of a G-type dimer structure linked by a β-5 bond (phenyl-coumaran). 49,54…”
Section: Resultsmentioning
confidence: 99%
“…4(A), indicating the presence of a G-type dimer structure linked by a b-5 bond (phenylcoumaran). 49,54 Overall, the MALDI-TOF MS analysis revealed that the extracted lignin had a maximum molecular weight of around 1374 Da and was made up of three repeating units. In addition, the results further consolidated the fact that SCB, HT1 and HT2 lignins are composed primarily of G-type b-5 dimers, acting as the repeating unit, linked by b-O-4 0 .…”
Section: Structural and Chemical Composition Of Extracted Ligninmentioning
confidence: 99%
“…Each of these compounds originates from different precursors, namely p-coumaryl, coniferyl, and sinapyl alcohols (Kai et al, 2018). Previously reported by Wei et al (2022), it was found that lignin precursors derived from coniferyl and sinapyl alcohols exhibit strong antibacterial activity against S. aureus.…”
Section: Introductionmentioning
confidence: 97%
“…Paracoumaryl alcohol, sinapyl alcohol, and coniferyl alcohol are lignin precursors from which phenyl propane units are formed, namely p-hydroxyphenyl (H), syringyl (S), and guaiacyl (G) units, respectively. The radical copolymerization of these units leads to the formation of lignin polymers [ 3 , 4 , 5 ]. Regarding structure, lignin is an amorphous, highly branched polymer containing ample amounts of functional groups, mostly methoxyl, phenolic, and aliphatic hydroxyl moieties.…”
Section: Introductionmentioning
confidence: 99%